PECULIARITIES OF SYSTEMIC LUPUS ERYTHEMATOSUS IN RUSSIANS AND GEORGIANS - Z S Alekberova; V A Nassonova; T M Reshetniak; V. G. Tzitlanadze; E. Y. Karteshvili; N Kalanadze (Научно-практическая ревматология)
Summary Comparative analysis of clinical manifestations and laboratory data in patients with SLE in different ethnic and race groups (Georgians and Russians) is presented.